Drought will not leave your glass empty : low risk of hydraulic failure revealed by long-term drought observations in world’s top wine regions - Charrier, Guillaume; Delzon, Sylvain; Domec, Jean Christophe; Zhang, Li; Delmas, Chloe E. L.; Merlin, Isabelle; Corso, Deborah; King, Andrew; Ojeda, Hernan; Ollat, Nathalie; Prieto, Jorge Alejandro; Scholach, Thibaut; et al. (2018)
Grapevines are crops of global economic importance that will face increasing drought stress because many varieties are described as highly sensitive to hydraulic failure as frequency and intensity of summer drought increase. We developed and used novel approaches to define water stress thresholds for preventing hydraulic failure, which were compared to the drought stress experienced over a decade in two of the world’s top wine regions, Napa and Bordeaux. We identified the physiological thresholds for drought-induced mortality in stems and leaves and found small intervarietal differences. Long-term observations in Napa and Bordeaux revealed that grapevines never reach their lethal water-potential thresholds under seasonal droughts, owing to a vulnerability segmentation promoting petiole embolism and leaf mortality. Our findings will aid farmers in reducing water use without risking grapevine hydraulic integrity.